Analisis pengaruh ketimpangan gender terhadap kemiskinan di Provinsi Gorontalo - Biludi, Anandia; Abdul, Irawati; Endang Saleh, Sri (Jurnal Paradigma Ekonomika, 2025)
Poverty is a multidimensional problem that remains a major development issue in Gorontalo Province. This study aims to analyze the effect of gender inequality on poverty in districts/cities of Gorontalo Province in the period 2019–2023. Poverty as the dependent variable is measured by the number of poor people in the districts/cities of Gorontalo Province, while the three indicators of gender inequality as independent variables are the ratio of female health workers to males, the ratio of the average length of schooling (RLS) of females to males, and the ratio of the labor force participation rate (TPAK) of females to males. This study uses a quantitative approach with a panel data regression method, using secondary data sourced from the Central Statistics Agency (BPS) of Gorontalo Province and the Gorontalo Provincial Health Office. Data analysis was carried out using the Fixed Effect Model (FEM) approach. The results of the study indicate that partially, health workers have a negative but insignificant effect on poverty, average years of schooling have a negative but insignificant effect on poverty, and labor force participation rate has a negative but significant effect on poverty. Simultaneously, all three variables have a significant effect on poverty in Gorontalo Province. These findings indicate that increasing gender equality, particularly through labor force participation, can contribute to poverty reduction in the districts/cities of Gorontalo Province.